2013
DOI: 10.1007/s10195-013-0275-6
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical comparison between locked 3.5-mm plates and 4.5-mm plates for the treatment of simple bicondylar tibial plateau fractures: is bigger necessarily better?

Abstract: BackgroundEvolution of periarticular implant technology has led to stiffer, more stable fixation constructs. However, as plate options increase, comparisons between different sized constructs have not been performed. The purpose of this study is to biomechanically assess any significant differences between 3.5- and 4.5-mm locked tibial plateau plates in a simple bicondylar fracture model.Materials and methodsA total of 24 synthetic composite bone models (12 Schatzker V and 12 Schatzker VI) specimens were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…Radiologic results were equally comparable in terms of rate and time of consolidation but also of quality of articular reduction, which highlights the stability of the reduction for the two types of implants, thus confirming biomechanical data [11].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Radiologic results were equally comparable in terms of rate and time of consolidation but also of quality of articular reduction, which highlights the stability of the reduction for the two types of implants, thus confirming biomechanical data [11].…”
Section: Discussionsupporting
confidence: 64%
“…Thus, according to our experience, in the short term there were few repercussions on the existence of malunions. To our knowledge, the clinical tolerance of locking plates was rarely studied, even though this was discusses by Hasan et al [11]. The different studies showed at the most the number of material ablations, with different figures ranging from 5 to 11 % [14,17,[25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, the introduction of the locking plate and rafting screw technique has greatly improved the treatment of severe tibial plateau fractures. [25][26][27] Furthermore, most anterior tibial plateau fracture-dislocations occur at a distance of approximately 1 to 2 cm from the joint surface, where the rafting screws in rafting technique are placed; therefore, the grip of the rafting screw on bone fragments would also be reduced. ►Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Also, for better stabilization of fragments in comminuted fractures, 3.5 mm screws or K-wire can be used near the articular surface with raft screws or wire ( 30 , 31 ). Moreover, there is no significant difference in the biomechanical properties between locked 3.5 mm and 4.5 mm plates ( 32 ). It has been shown that in cancellous bone, 3.5 mm screws have equivalent pullout strength in comparison to 4.5 mm and 6.5 mm screws ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%